Country Income Is Only One of the Tiles: The Global Journey of Antimicrobial Resistance among Humans, Animals, and Environment - Angela Pieri; Richard Aschbacher; Giada Fasani; Jole Mariella; Lorenzo Brusetti; Elisabetta Pagani; Massimo Sartelli; Leonardo Pagani (MDPI AG, 2020)
Antimicrobial resistance (AMR) is one of the most complex global health challenges today: decades of overuse and misuse in human medicine, animal health, agriculture, and dispersion into the environment have produced the dire consequence of infections to become progressively untreatable. Infection control and prevention (IPC) procedures, the reduction of overuse, and the misuse of antimicrobials in human and veterinary medicine are the cornerstones required to prevent the spreading of resistant bacteria. Purified drinking water and strongly improved sanitation even in remote areas would prevent the pollution from inadequate treatment of industrial, residential, and farm waste, as all these situations are expanding the resistome in the environment. The One Health concept addresses the interconnected relationships between human, animal, and environmental health as a whole: several countries and international agencies have now included a One Health Approach within their action plans to address AMR. Improved antimicrobial usage, coupled with regulation and policy, as well as integrated surveillance, infection control and prevention, along with antimicrobial stewardship, sanitation, and animal husbandry should all be integrated parts of any new action plan targeted to tackle AMR on the Earth. Since AMR is found in bacteria from humans, animals, and in the environment, we briefly summarize herein the current concepts of One Health as a global challenge to enable the continued use of antibiotics.